Pengembangan Perangkat Pembelajaran Fisika Berbasis Inkuiri Terbimbing Berbantuan Eksperimen Untuk Meningkatkan Penguasaan Konsep Siswa - Sri Wahyuni; Kosim Kosim; Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2018)
The study aims to develop physics learning device based guided inquiry with experiments that valid, practical, and effective to improve studentsÃ¢â¬â¢ mastery concept. The research stages refers to Borg & Gall's model from preliminary studies to main field testing. The validity data is obtained from the assessment for the feasibility of learning devices by experts, then analysed to determine the level of validity. Expert advice is used to revise the learning device. Learning device was implementation to test the practicality and effectiveness of learning device to improve students' mastery concept. The results of the study show that learning device are very valid category. Result of the trial based on the data of learning implementation show that learning device are in the practical category.ÃÂ Guided inquiry model with an experiment in learning physics effective to improve studentsÃ¢â¬â¢ mastery concept. Increased students mastery concept on cognitive aspect remembering (C1), understanding (C2), applying (C3) and create (C6) in high categories, while the cognitive aspect analyzing (C4) and evaluating (C5) in the medium category.